The development of Chinese fir plantations undergo significant changes in soil microbial metabolic function and enzyme activities. Issue 4 (4th July 2019) - Wang, Chaoqun; Xue, Lin; Dong, Yuhong; Hou, Lingyu; Wei, Yihui; Chen, Jiaqi; Jiao, Ruzhen
ABSTRACT: Comprehensive evaluation of soil enzyme activities, microbial community diversity can provide a theoretical basis for the sustainable management of the plantations. In this study, we analyzed soil enzyme activities and the metabolic functional diversity of the microbial communities of Chinese fir plantations aged 3 years, 12 years and 38 years. The results showed that the high-age (38 years old) was beneficial to soil microbial community diversity. The activities of catalase and urease, the average well colour development (AWCD) values for carbon sources used by microbial communities and five diversity indices all showed a gradual increase as trees aged from 3 years to 38 years. Sucrase activity decreased by 109% from 3- to 12-year-old plantations and increased by 139% from 12- to 38-year-old plantations. Overall, the stand age is an important factor for driving changes in soil properties of Chinese fir plantations, and high age may be more conducive to the improvement of soil properties, especially enzyme activities and microbial community diversity, which is of great significance to the screening of key indicators for the establishment of precision evaluation technology in Chinese fir sites.